Infantile colic: looking to old data through new eyes - Francesco Savino; Maria Garro; Silvia Nicoli; Simone Ceratto (Hygeia Press di Corridori Marinella, 2015)
This paper performs an overview about researches and clinical trials on gut microflora and the use of probiotics, and seeks to define a new picture of current literature in order to propose an evidence-based practice approach for the treatment of infantile colic. Colics are a self-limiting, benign and widespread disturbance in the first three months of life, but provide a great disturbance on family life, also because this condition is frequently undervalued by physicians and available literature doesn't provide univocal indication about management and treatment. Literature reports growing evidences about the effectiveness of dietary approach or supplementation with probiotics. This article tries to evaluate available evidences through GRADE system, in order to underline limitations, inconsistency and publication bias of old clinical trials. However, this choice could provide multiple and discordant results. According to the growing of new systematic reviews, evaluations about evidences and recommendations in health care are complex, and might show up different results. Moreover, up to date many different definitions and outcome measures for infantile colic have been proposed in clinical trials: many take in account crying time, but a minor part also consider parental perception. The effectiveness of complementary and alternative treatments and behavioural interventions needs to be further investigated. Recently, the possible action of microbiota as a cause of colics and the use of some probiotic strains for the treatment have raised great interest. It has been also postulated that parent-infant interaction may influence infantile colic, but further researches on educational and psychological intervention are required in order to better clarify this issue, as well as further investigations are needed in order to provide more reliable evidence-based guidelines.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)